Efektivitas Model Konseling Behavioral dengan Teknik Relaksasi untuk Meminimalisasi Kecemasan dalam Menghadapi Mata Pelajaran Matematika - Ni Komang Sri Yuliastini (Universitas Kanjuruhan Malang, 2020)
The objectives of this study are (1) to describe the implementation of individual counseling, (2) to determine the effectiveness of the behavioral counseling model with relaxation techniques to minimize students' anxiety in facing Mathematics at SMK PGRI 4 Denpasar. This study answered four problem formulations: (1) behavioral counseling with relaxation techniques at SMK PGRI 4 Denpasar has not been implemented because guidance and counseling teachers do not have a clear model related to the procedures for implementing behavioral counseling with relaxation techniques, (2) a behavioral counseling model with effective relaxation techniques in Minimizing anxiety in facing Mathematics at SMK PGRI 4 Denpasar according to the regionalcoxon statistical test results showing the Wilcoxon value of 0.028 <0.05 and a decrease in the results of interpretation and postage by 47.83 points. Counseling teachers are advised to apply the behavioral counseling model with relaxation techniques because this service is proven to be effective in minimizing anxiety in facing Mathematics at SMK PGRI 4 Denpasar.